AN ECONOMIC ANALYSIS OF ADOPTION OF PRICE FORECASTS AND ITS IMPACT ON DECISION MAKING IN CHILLI FARMING - A. INDHUSHREE; G. RAGHUNADHA REDDY (The Journal of Research ANGRAU, 2015)
The present study (2014-15) was conducted in Guntur district of Andhra Pradesh to analyse the factors influencing adoption of price forecasts and to study the impact of price forecasts on decision making of the chilli farmers. The study revealed that education level, possession of communication assets by farmers, average annual income of farmers and source of market intelligence to farmers were the significant factors influencing the adoption of price forecasts by farmers. Price forecast was found to have positive impact on farm decision making. The impact of adoption of price forecasts was high in case of decision on quantity of chilli to sell followed by decision on storage of produce, allotting the area of land for chilli. The impact was also observed in case of decision regarding selection of crops time of harvesting and time of sowing.